The impact of partial discharge on the dielectric properties of refined bleached and deodorized palm oil (RBDPO) - HadiAlnashia, Ilham A.; Izzeldin, I. Mohd; Almelian, Mohamad Milood; Omran, Mohamed Asghaiyer (UTeM, 2018)
Several years ago, insulation oil played an important role in electrical power equipment. Mineral oil extracted from petroleum resources (a non-renewable source) has been widely used as an insulating material in the transformers. Therefore, there is a need to find renewable alternatives to the petroleum-based mineral oil. Refined bleached and deodorized palm oil (RBDPO) is a palm-based oil which has undergone several modifications. In this paper, the dielectric properties of RBDPO and the conventional transformer oil were investigated, followed by an investigation of its partial discharge (PD) impact on the dielectric properties. The breakdown voltage was measured according to the international electrotechnical commission (IEC 6056) standard and the viscosity test was done according to BS EN ISO 3104:1996. The experiments have proved that RBDPO can be used as an insulating oil due to the closeness of its dielectric properties compared to the conventional oil.